Cancer Stem Cells: Emergent Nature of Tumor Emergency - Efremov, Yaroslav R.; Proskurina, Anastasia S.; Potter, Ekaterina A.; Dolgova, Evgenia V.; Efremova, Oksana V.; Taranov, Oleg S.; Ostanin, Aleksandr A.; Chernykh, Elena R.; Kolchanov, Nikolay A.; Bogachev, Sergey S. (Frontiers in Genetics, 2018)
A functional analysis of 167 genes overexpressed in Krebs-2 tumor initiating cells was performed. In the first part of the study, the genes were analyzed for their belonging to one or more of the three groups, which represent the three major phenotypic manifestation of malignancy of cancer cells, namely (1) proliferative self-sufficiency, (2) invasive growth and metastasis, and (3) multiple drug resistance. 96 genes out of 167 were identified as possible contributors to at least one of these fundamental properties. It was also found that substantial part of these genes are also known as genes responsible for formation and/or maintenance of the stemness of normal pluri-/multipotent stem cells. These results suggest that the malignancy is simply the ability to maintain the stem cell specific genes expression profile, and, as a consequence, the stemness itself regardless of the controlling effect of stem niches. In the second part of the study, three stress factors combined into the single concept of "generalized cellular stress," which are assumed to activate the expression of these genes, were defined. In addition, possible mechanisms for such activation were identified. The data obtained suggest the existence of a mechanism for the de novo formation of a pluripotent/stem phenotype in the subpopulation of "committed" tumor cells.